PERBEDAAN INTERVENSI WOBBLE BOARD EXERCISE DENGAN 4 SINGLE LIMB HOPPING EXERCISE UNTUK MENINGKATKAN STABILITAS ANKLE PADA KASUS SPRAIN ANKLE KRONIK (Lembaga Penerbitan Universitas Esa Unggul, 2018)
Purpose: to determine difference effect of Wobble Board exercise with 4 single limb hopping exercise on ankle stability in chronic ankle sprain. Methode: the research is purposive experiment, where an increase in the value of stability ankle measured using stability test. The sample consisted of 16 subject from futsal players, randomly selected to be devided into two groups. The treatment group I consists by 8 samples with the Wobble Board exercise meanwhile treatment group II consisted of 8 samples with 4 single limb hopping exercise. Results: data which obtained from normality test with Shapiro Wilk test is normal, meanwhile data from Leven’s test resulted in homogen variant. The results of hypothesis testing in the treatment group I with Paired Sample t-Test is, p value = 0.000 for stability test, which means Wobble Board exercise can improve the ankle stability. In the treatment group II Paired samples t-test, p value = 0.003 for the stability test, which means 4 single limb hopping exercise can improve the ankle stability. On the Independent Sample t-Test showed 0.65 for the value of the stability test, which means Wobble Board exercise same as 4 single limb hopping exercise in improving the stability ankle. Conclusions: Wobble Board exercise same as 4 single limb hopping exercise in improving the ankle stability in chronic ankle sprain. Keywords: Wobble Board exercise, 4 single limb hopping exercise, stability ankle, stability test, futsal players